2018
DOI: 10.1111/cea.13108
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilia, gelatinase release and microvascular leakage induced by human mast cell tryptase in a mouse model: Lack of a role of protease‐activated receptor 2 (PAR2)

Abstract: SummaryBackgroundTryptase, the most abundant protease of the human mast cell, has been implicated as a key mediator of allergic inflammation that acts through activation of PAR2.ObjectivesTo investigate the contribution of PAR2 in the pro‐inflammatory actions mediated by tryptase in a mice model.MethodsWe have injected recombinant human βII‐tryptase into the peritoneum of PAR2‐deficient and wild‐type C57BL/6 mice. After 6, 12 and 24 hours, mice were killed, peritoneal lavage performed and inflammatory changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…PARs activate ERK1/2, JNK, and p38 MAPKs to induce cellular responses in the brain cells that also induces the secretion of inflammatory cytokines and chemokines [67]. Previous study has shown that mast cell proteases upregulate neuroinflammation via activating glial cells and neurons to release TNF-α and IL-6 through PAR-2 expression [71]. PAR-2 expressed on glia, neurons and mast cells upregulate neuroinflammation in the CNS [7275].…”
Section: Discussionmentioning
confidence: 99%
“…PARs activate ERK1/2, JNK, and p38 MAPKs to induce cellular responses in the brain cells that also induces the secretion of inflammatory cytokines and chemokines [67]. Previous study has shown that mast cell proteases upregulate neuroinflammation via activating glial cells and neurons to release TNF-α and IL-6 through PAR-2 expression [71]. PAR-2 expressed on glia, neurons and mast cells upregulate neuroinflammation in the CNS [7275].…”
Section: Discussionmentioning
confidence: 99%
“…After birth, its expression is present in large cells on bone surfaces, presumably osteoclasts [ 34 ]. Recently, MMP-9 expression was related to the number of neutrophils present in the inflammatory zones [ 35 ]. MMPs, in general, are involved in apical periodontitis through their relationship with the clinical characteristics of the disease, in the severity of bone destruction, and tend to have an increased expression in lesions greater than 7 mm, especially MMP-1, 2 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 However, others reported that the number of infiltrated mast cells in BP lesional skin is not increased compared to healthy controls and does not correlate with pruritus severity. 39 Taken together, mast cellderived histamine likely does not play a significant role in BPassociated pruritus or may contribute exclusively to the pruritus Dupilumab (BP) [68][69][70] Tralokinumab, lebrikizumab 72 IL-31 Activation of IL-31 receptor A (IL-31RA) and oncostatin M receptor (OSMR) on cutaneous sensory neurons [77][78][79][80][81][82][83] • Inconsistent serum levels in BP 74,84,85 Tryptase Activation of PAR-2 receptor and direct stimulation of cutaneous sensory neurons [110][111][112][113] • Elevated levels in BP blister fluid and sera [118][119][120] • Tryptase-positive mast cells in BP b39 • Increased tryptase-positive cells in LAD 122 -Nafamostat…”
Section: Histamine In Pemphigoid Diseasesmentioning
confidence: 99%